Tantangan Kurikulum 2013 Untuk Menghadapi Pembelajaran di Era Modern - Primanita Sholihah Rosmana; Sofyan Iskandar; Masruroh Masruroh; Metaninda Permata Ayu; Anis Hidayatul Ummah (FONDATIA, 2022)
The rapid advancement of data and correspondence innovation in all areas of life has marked the beginning of the 21st century. the Indonesian government for this situation continues to strive to further develop the parts of teaching at each level economically by changing the world of training improvement. One of them is to implement 21st century inventive learning structures. The type of technique used in this research is library research. This strategy limits its implementation to only using library resources to obtain research information, without directing field research, collecting library information, perusing, recording, and handling disparate data on improving education plans in Indonesia to face the demands of 21st century capabilities through various related sources. The basic standards of 21st century learning include: training must be cooperative (teaching must work together), learning must be organized (learning must have organization), guidance must be student focused (learning focused on students), schools should be included with the community (schools should be coordinated with the local area). There are two things such as two basic methodologies in the discovery of K-13 which are very closely related to the needs of the 21st century, namely demand and logical methodologies that are used as references in creating different 21st century inventive learning models.